Development and Application of High-Efficiency Cleaning Device for Subway Based on Self-Generating Energy Storage System. Issue 3 (February 2020) - Peng, Yucheng; Wang, Yanlong; Zhou, Jie
Abstract: In view of the current manual cleaning of the subway track, it requires more personnel, lower efficiency, and more capital needs. Therefore, a new method can be developed, which adopts a combination of a billboard and a cleaning device, so as to satisfy the advertising efficiency, the garbage on the subway track can be cleaned more conveniently, efficiently and environmentally. Among them, the subway station demonstrates that the method can be used by using design simulation experiments, and the rationality of the structure of the device is obtained.